Energy Potential of Animal Waste in the State of Paraná (Brazil) - Fabrízio Nicolai Mancini; Jackson Milano; Joilson Gonçalves de Araújo; Karen Techy Iastrenski; Nicolli Sperança Silveira; Rodrigo Creuz Pertile (Brazilian Archives of Biology and Technology, 2019)
Abstract Animal biomass is a source of energy commonly discarded without or with low utilization, but its availability draws attention to its reuse [1]. The utilization can be carried out in different ways, varying in terms of generation time and efficiency. The use of biodigestion requires a relatively small area compared to landfills or natural composting, and it provides other materials besides biogas, that can be recycled as fertilizer and has a short residence time of residues [2]. The energy supplied as biogas can be harnessed as heat or electricity in case of conversion. Considering the energy needs of animal husbandry and the ease of reinsertion of energy in the production cycle, the possibility of distributed generation of biogas was studied as a way to complement the rural energy consumption matrix. Poultry farms require heat for chicks [3], dairy production centers require sterilization of used equipment [4] and pig farms require good heating systems to ensure animal weight gain [5]. In this way, the production can take advantage of the heat of the gas without the conversion into electricity, minimizing losses. Creation centers themselves can also generate electricity, eliminating the need for large transmission lines.